2018
DOI: 10.1080/03019233.2018.1552773
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between crystallization and break temperature of mould flux

Abstract: Many researchers believe that crystallization is responsible for drastic viscosity changes near the break temperature of mould flux; however, there are no reasonable experimental data to support this view. In this study, the complete crystallization process is recorded in situ by inhibiting the volatilization of fluoride, and the relationship between viscosity change and crystallization near the break temperature is studied. Mould flux with a basicity of 0.65 had no break temperature, and no crystallization oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The relationship between the break temperature measured at rotation viscometer, and the onset of crystallization measured with thermal analysis apparatus, was already studied; it was reported that the crystallization temperature agrees well with the break temperature in some cases, and in other cases does not [10]. Besides, it was also reported that crystallization temperature should be higher than break temperature measured with rotation viscometer, because the break point is not related to the first crystals precipitation, but instead to a critical volume fraction of crystals; depending on mould flux composition, this volume varies [11].…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between the break temperature measured at rotation viscometer, and the onset of crystallization measured with thermal analysis apparatus, was already studied; it was reported that the crystallization temperature agrees well with the break temperature in some cases, and in other cases does not [10]. Besides, it was also reported that crystallization temperature should be higher than break temperature measured with rotation viscometer, because the break point is not related to the first crystals precipitation, but instead to a critical volume fraction of crystals; depending on mould flux composition, this volume varies [11].…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in Na 2 O content was likely to be attributed to the evaporation as gaseous species or was reduced by Al in the liquid steel. Our group has tested that the volatilization ratio ranged from 0.5 to 1.25 mass% for four CaO–SiO 2 –Al 2 O 3 –MgO–Na 2 O–F mold fluxes with about 6–12 mass% of Na 2 O content. Kim et al also reported that Na 2 O would be reduced by Al in the molten steel due to less SiO 2 or high Al in the steel.…”
Section: Resultsmentioning
confidence: 99%
“…However, the in situ observation of the crystallization of mold slag with different basicities in this study indicated that when basicity exceeded 1.45, the temperature at which the cuspidine crystal started to precipitate was reduced. [30] Therefore, the break temperature initially increased and subsequently decreased, as shown in Figure 2a. The evolution of the melting temperature illustrated in Figure 2b exhibits the same trend as the break temperature.…”
Section: Strategy To Achieve Mold Slag With High Basicity and Adequat...mentioning
confidence: 89%